Behavior of 1%Cr Steels at Fluidized Bed Nitrocarburizing - Sorin DOBROVICI; Nelu CAZACU; Adolf BÂCLEA; Elena DRUGESCU; Nelu PREDA (The Annals of “Dunarea de Jos” University of Galati. Fascicle IX, Metallurgy and Materials Science, 2006)
Paper is based by nitrocarburizing experiments made on laboratory plant. For experiments were used different samples of steel at different nitrocarburizing regimes. Influence factors were: temperature and ammonia concentration. Treatment time had a constant value 2h30min. Influences of factors were investigated by: samples mass modifications, surface structure (micrograph), layer depth to all samples and hardness HV5 on the surface. The results confirm possibility to use fluidized bed like nitrocarburizing media and good behaviour of steel.